Evan’s Index Values and Its Relationship with Individual Characteristics (Age and Gender) in Head CT-Scan Examination at Haji Adam Malik Hospital Medan 2021-2022 - Zamzami, Muhammad Avicienna; Daulay, Elvita Rahmi; Indharty, Suzy (CoinReads Media Prima, 2023)
Introduction: Enlargement of the ventricles caused by disturbances in the production, flow, and absorption of cerebrospinal fluid is known as hydrocephalus.Radiological examinations such as computed tomography (CT) play an important role in establishing the diagnosis of hydrocephalus. Assessment of ventricular enlargement in most cases is done subjectively and based on radiological experience. Objectively, ventricular size can be assessed by linear ratios on CT. Evan's index (EI) is the simplest and most reliable method for assessing ventricular size. Age and sex have an influence on the size of the ventricles. The aim of this study was to determine the average Evan's Index and its relationship with individual characteristics (age and sex) in patients who underwent head CT scans at H. Adam Malik General Hospital, Medan. Method: This study used a case series design to determine the relationship between individual characteristics (age and gender) with the Evan's Index value and to obtain an average normal Evan's Index value in patients who underwent head CT scans at the Haji Adam Malik General Hospital in Medan. Results: : The highest sample age was in the 19-30 year age group, namely 39 people (35%). In this study, there were more female subjects, namely 51% compared to males (49%). Mean + standard deviation and median (min-max) in Evan’s Index data were 0,26 + 0,03 and 0,25 (0,2-0,36). There was a significant correlation between age and the Evan's Index (p <0.001) with a moderate degree of correlation (0.442). There was no significant relationship between gender and Evan's Index (p=0,121; ηp2=0,022). There was no significant difference between education levels and the average Evan's Index (p=0.434). Conclusion: There is a relationship between the increase in the age group of the participants and the increase in the EI value which is linear and correlative. There was no difference in EI values between gender and level of formal education regardless of the age group of the individuals analyzed.